THE RELATIONSHIP BETWEEN SOCIAL INTERACTION AND SELF-CONCEPT OF SMAIT 'ALAMY SUBANG STUDENTS - Luthfiyyah, Salwa (Politeknik Kesejahteraan Sosial Bandung, 2025)
Adolescents need attention in their developmental phase, through social interaction adolescents gain knowledge related to the values they may believe in, this can be a factor in the formation of self-concept in adolescents. This study aims to determine the relationship between social interaction and self-concept formation in X and XI grade students of SMAIT 'Alamy Subang. This study used a quantitative approach with a descriptive correlational research design, and sample selection in the form of purposive sampling method. Data collection techniques used in the form of social interaction questionnaires and self-concept to respondents as many as 41 students. Data analysis techniques in this study used nonparametric statistical methods with Spearman Rank correlation. Data processing was carried out using IBM SPSS Statistics Version 30.0.0. The results showed a correlation coefficient of 0.585, which means that the level of strength of the relationship between variables is a strong relationship. It is known that the value of Sig. (2-Tailed) of 0.001, then the value of Sig. (2-Tailed) <0.05, which means there is a significant relationship between social interaction and self-concept. Then the null hypothesis (Ho) is rejected, while the alternative hypothesis (HA) is accepted. This means that there is a significant relationship between social interaction and self-concept of SMAIT 'Alamy Subang students which has a strong level of relationship strength and positive direction. Therefore, improving communication and self-confidence, as well as the role of family support are important factors in the formation of a good self-concept.